Exploring the perspectives of graduating construction field students on drone technology applications in construction projects - Zainal Abidin, Zaiwannizar; Md Zain, Noraini; Zainuddin, Mohd Firdaus; Abdullah, Mohd Nazri; Abu Bakar, Norbaizura; Che Mat, Muhammad Ammar Husaini (Journal of Islamic, Social, Economics and Development, 2025)
As drone technology continues to reshape global construction practices, its adoption in Malaysia remains limited, raising questions about the readiness of future construction professionals to embrace this innovation. This study investigates the perspectives of final-year construction field students in Malaysia regarding the applications and implementation barriers of drone technology in construction projects. A quantitative survey was conducted among 103 students from 3 universities in Malaysia which are Universiti Teknologi Malaysia (UTM), Universiti Sains Malaysia (USM), and Universiti Teknologi Mara (UiTM), utilizing purposive sampling and a structured questionnaire distributed via Google Forms. The findings reveal that students demonstrate a moderate to high level of awareness, particularly in areas such as progress tracking, visual inspection, and survey mapping. However, significant barriers persist, including complex legal regulations, technical limitations, and financial constraints, which may hinder wider industry adoption. This study highlights the need for enhanced educational exposure, regulatory clarity, and strategic investment to equip the next generation of professionals with the competencies required to integrate drone technology into mainstream construction practices.